Modeling factors for industry experts’ intention to participate in online scaffolding - Hajar Abdullah, Aznur; Tse. Kian, Neo; ., . (International Journal of Engineering and Technology, 2018)
The participation of industry experts in problem-based learning (PBL) activities helps in improving university studentsâ€™ problem solving skills considering industry experts have more experiential knowledge. Online scaffolding, a form of assistance provided by industry experts via myriad use of ICT applications allows knowledge to be transcendent beyond the classroom boundaries is seen as an opportunity to improve deterioration of problem solving skills among university students. This study intends to investigate factors that may affect the intention of industry experts to provide structural empowerment of resources, information, support and opportunity for learning in online scaffolding. Modeling the right factors via the application of empowerment theory may help to improve understanding on factors that may motivate or hinder industry experts to provide the structural empowerment. Necessary national education policy can be formulated for higher education institutions (HEIs) prior inviting industry experts to be part in online PBL initiative. Based on existing literature, trust, ICT anxiety and perceived ease of use are identified as factors that may influence industry experts to provide structural empowerment.Â Â